Formal methods and software engineering : 17th International Conference on Formal Engineering Methods, ICFEM 2015, Paris, France, November 3-5, 2015 : proceedings /: 17th International Conference on Formal Engineering Methods, ICFEM 2015, Paris, France, November 3-5, 2015 : proceedings. (2015) - Unknown
No abstract available